Local density approximation of spherically symmetric atomic ground states - Stojanovič, Blaž (Matrika, 2020)
The first part of this article discusses the problem of electronic structure and its solutions using density functional theory. First the Hohenberg-Kohn theorems are stated and proved, then the Kohn-Sham auxiliary system is derived using their ansatz and finally different approximations of the exchange correlation functional are discussed. The second part focuses on the numerical implementation of the restricted spherically symmetric local density approximation. This method is then used to calculate atomic ground-states and their first ionisation energies. The results are compared with experimental data and show good agreement.
Keywords: atomic physics; atomska fizika; density functional theory; electronic structure; elektronska struktura; local density; lokalna gostota; metoda gostotnih funkcionalov